2014
DOI: 10.1080/09593330.2014.881421
|View full text |Cite
|
Sign up to set email alerts
|

Influence of soil pH in vegetative filter strips for reducing soluble nutrient transport

Abstract: Low efficacy of vegetative filter strips (VFS) in reducing soluble nutrients has been reported in research articles. Solubility of phosphorus and nitrogen compounds is largely affected by pH of soil. Changing soil pH may result in a decrease in soluble nutrient transportation through VFS. This study was conducted to evaluate the effect of pH levels of VFS soil on soluble nutrient transport reduction from manure-borne runoff. Soil (loamy sand texture; bulk density 1.3 g cm-3) was treated with calcium carbonate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…While the VGFs slow the speed of overland flows, the efficacy can vary significantly and is less well described for underground movement. Slope (Kouznetsov et al 2007), surface area, width, soil (Rahmana et al 2014), rainfall (Blaustein et al 2016), topography and hydrology can all influence the variability. Recent work has emphasized the role of preferential flow, particularly during saturation, heavy rainfall and formation of surface gullies and eddies phenomena and in particular for the environmental fate of hydrophilic compounds (Allaire et al 2015) and colloids or colloidal bound contaminants or microorganisms (Mohanty et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While the VGFs slow the speed of overland flows, the efficacy can vary significantly and is less well described for underground movement. Slope (Kouznetsov et al 2007), surface area, width, soil (Rahmana et al 2014), rainfall (Blaustein et al 2016), topography and hydrology can all influence the variability. Recent work has emphasized the role of preferential flow, particularly during saturation, heavy rainfall and formation of surface gullies and eddies phenomena and in particular for the environmental fate of hydrophilic compounds (Allaire et al 2015) and colloids or colloidal bound contaminants or microorganisms (Mohanty et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Since cation exchange is the main mechanism of K binding to solid phases and soluble complexes does not form in the case of this cation, the importance of competition with protons is less than other specific binding cations (Almas et al 2007). Thus, the effect of pH on K solubility is less significant than Ca and Mg. Almas et al (2007) observed the reduction of cations solubility following the pH increase and suggested that both Ca and Mg have the ability for specific binding with solid phases and thus, the pH change is more effective in the case of Ca and Mg solubility than K. In the work of Rahman et al (2014), increasing the pH lowered the concentration of K in runoff, but pH change generally did not have significant effect on K solubility. Jalali (2006) suggested that in calcareous soils, there is a high H + -buffering capacity and the release of K from minerals in these soils could be affected by pH of the soil.…”
Section: Resultsmentioning
confidence: 93%
“…The excessive loss of positive charge relative to anion dissolution near the pH 8 is the possible reason for the observed increase in P concentration toward this pH (Oburger et al 2011). Rahman et al (2014) described that over the pH 7.5, the availability of Al and Fe oxides and thus adsorption of P by these compounds diminishes. Some researchers have reported the increase in P concentration following the pH raise (Madrid and Posner 1979;Cabrera et al 1981;De Smet et al 1998;Sato 2003), and some observed the enhancement of P concentration with pH reduction (Rupa et al 2001;Barrow 2002).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Lee et al [5] found that the mixed switchgrass and wood buffer had a particularly higher capacity for removing the sediment, TN, and TP than the switchgrass buffer. Rahmana et al [23] studied the effects of soil pH changes on the VFS performance and found that changing soil pH affected soluble nutrient transportation through VFS.…”
Section: Introductionmentioning
confidence: 99%